Student Educating Experience in the New Digital Education - E. V. Strogetskaya; E. A. Pashkovsky; N. V. Kazarinova; I. B. Betiger; A. V. Timofeev (Дискурс)
Introduction. The paper is devoted to a review of the main issues that digitalization poses for higher education sociologists. Readers are also offered the results of an empirical study aimed at obtaining answers to some of these questions by analyzing the direct experience of students who have completed online courses and express their views on its functional characteristics and performance.Methodology and sources. As a methodological framework for the study, the authors used a poly-paradigmatic approach, including the provisions of the economy of higher education, the principles and methods of the institutional tradition of the sociology of education, the ideas of theoretical concepts of social representations and communicative action.Results and discussion. The results of two sociological studies carried out in the form of questionnaires are presented. The target audience of the surveys were first-year undergraduates in technical areas of training who did not have direct experience of smart education at the university, and undergraduate students who took various online courses as part of their educational process.According to the survey, undergraduates have a clear interest in smart education and are independently looking for open online courses. However, they do not clearly assess some of the advantages of digital technology, for example, the ability to repeat the explanation. Undergraduate students, regardless of the course, direction and form of study, prefer the hybrid format over online courses and traditional classroom instruction. The most important aspects of online learning for students were identified: the clarity and consistency of the presentation of educational material, the usefulness of the course for the specialty, the entertaining course. At the same time, the image side of the presentation of materials by the teacher is of much less interest to them than the developers of the courses.As a result of the research, the most interesting topics for future discussions about the functional characteristics and effectiveness of smart education, as a new educational paradigm, are the following paradoxes: weak interest (or even lack thereof) of students in the possibility of a digital learning format such as individual and collective feedback, the possibility of organizing forums and conducting group discussions of the issues under study without/with the participation of a teacher; the contradictions between the targets of teachers-developers of online courses and the educational needs of students-users of online courses.Conclusion. The authors of the paper revealed a generally positive attitude of students to smart education. Most noted that it is more interesting to study online, however, classes based on the traditional form provide more solid and clear knowledge. The most effective and functional version of teaching practices seems to be hybrid courses, which allow combining the advantages of the "classical" and the new digital education paradigms.